Efektivitas Organisasi Wanita Islam Alkhairaat (WIA) dalam Pengembangan Dakwah di Kota Palu - Ikram, Moh.; Syamsiyatun, Siti; Rifa’i, Ahmad (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
This research aims to explore the effectiveness of Wanita Islam Alkhairaat (WIA) in da'wah development in Palu City. Using a qualitative approach and case study method, this research analyses the da'wah programs implemented by WIA as well as the factors that influence its effectiveness. Data were collected through in-depth interviews with WIA administrators and the community involved, as well as direct observation and document study related to WIA activities. The results showed that WIA has implemented various da'wah programmes that successfully empower women and increase public awareness of Islamic values. However, there are supporting and inhibiting factors that affect the effectiveness of da'wah, such as community support, limited resources, and challenges in reaching a wider audience, especially in Eastern Indonesia such as North Kalimantan, Gorontalo, North Maluku, West Papua, and other provinces. This research is expected to contribute to the literature on the role of Islamic women's organisations in da'wah, as well as provide recommendations for improving the effectiveness of WIA's da'wah activities in the future. To overcome these challenges, a sustainable effort is needed from WIA in increasing the internal capacity of its members in all regions in Eastern Indonesia, especially in Palu City, Central Sulawesi.